Revelation - Fanning, Buist M. (Grand Rapids : : Zondervan, 2020)
"Designed for the pastor and Bible teacher, the Zondervan Exegetical Commentary on the New Testament features today's top New Testament scholars and brings together commentary features rarely gathered together in one volume. With careful analysis and interpretation of the Greek text, the authors trace the flow of argument in each New Testament book, giving readers the tools they need to properly understand and communicate the meaning of the text. Commentary on each passage follows a clear structure to help readers grasp the flow and meaning of the text: Literary Context: A brief discussion of how the passage functions in the broader literary context of the book. Main Idea: A one- or two-sentence statement of the big idea or central thrust of the passage. Translation and Graphical Layout: Presents each commentator's translation of the Greek text in a graphical layout to help the reader visualize, and thus better understand, the flow of thought within the text. Structure: Describes the flow of thought in the passage and explains how certain interpretive decisions regarding the relationship of the clauses were made in the passage. Exegetical Outline: The overall structure of the passage is described in a detailed exegetical outline. This will be particularly helpful for those who are looking for a way to concisely explain the flow of thought in the passage in a teaching or preaching setting. Explanation of the Text: Commentators examine words and images, grammatical details, relevant Old Testament and Jewish background to a particular concept, historical and cultural context, important text-critical issues, and various interpretive issues that surface. Theology in Application: The theological message of the passage is summarized. The author discusses the theology of the text in terms of its place within the book and in a broader biblical-theological context. Finally, each commentator provides some suggestions on what the message of the passage is for the church today.The Zondervan Exegetical Commentary on the New Testament series is the go-to resource for pastors and Bible teachers looking for deep but accessible study that equips them to connect the needs of Christians today with the biblical text"-- Provided by publisher. "The Zondervan Exegetical Commentary on the New Testament series is the go-to resource for pastors and Bible teachers looking for deep but accessible study that equips them to connect the needs of Christians today with the biblical text"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Bible. Revelaton--Commentaries.; RELIGION / Biblical Commentary / New Testament